ChemInform Abstract: Indole Synthesis Through Sequential Electrophilic N—H and C—H Bond Activation Using Iodine(III) Reactivity. Issue 32 (22nd July 2016) - Fra, Laura; Muniz, Kilian
Abstract: Four different conditions A)—D), which all contain an iodine agent in either stoichiometric or catalytic amount, are elaborated for the cyclization of aromatic sulfonamide precursors bearing an alkyne side chain, as is demonstrated for the examples (Ia) and (Ib).